Physiological and anatomical differentiation of two sympatric weed populations - Barbara Neuffer; Michael Schorsch; Steffen Hameister; Johannes Knuesting; Jennifer Selinski; Renate Scheibe (PeerJ, 2020)
In the vineyards of Rhineland-Palatinate (Germany), two different types of Shepherd’s Purse (Capsella bursa-pastoris) coexist: (1) the common type called ‘wild type’, and (2) the decandric type called Capsella apetala or ‘Spe’ with four stamens in place of the four petals. In this study, we compare the anatomical and physiological characters of rosette leaves of the respective types. Progeny of individual plants was cultivated in growth chambers under low- and high-light conditions. Under low-light conditions, the stomata densities of the adaxial and abaxial epidermis did not differ between the two types. When grown under high-light conditions, wild type and Spe, both exhibited increased stomata densities compared to low-light conditions, but Spe to a lesser extent than the wild type. The maximal photosynthetic capacity of Spe was lower in both, low-light and high-light conditions compared to wild-type plants. Under all CO2 concentrations, Spe seemed to be less productive. The less effective CO2 assimilation of the Spe mutant C. apetala was accompanied by later flowering. This fact prolonged the vegetative phase of Spe by about two weeks and was sufficient for the maintenance of both populations stably over years.